Antipsychotic Polypharmacy: Still Dirty, But Hardly a Secret. A Systematic Review and Clinical Guide - K. Tracy, Derek; Sendt, Kyra-Verena; S. Shergill, Sukhwinder (Current Psychopharmacology, 2013)
Treatment resistant psychoses present an enormous burden. Guidelines generally prohibit more than one antipsychotic and the efficacy of this is limited, but multiple surveys suggest such practice is common. Reasons for this include a lack of alternatives, difficulty in discontinuing, successful clinical experience, and inertia. We performed a systematic review on the efficacy of antipsychotic polypharmacy. This identified two broad categories of polypharmacy - clozapine plus a second antipsychotic and two ‘non-clozapine’ antipsychotics - and three domains of efficacy - effects on specific symptoms, cognition, and adverse effects. The evidence is mixed. There are high quality double blind studies supporting clozapine augmentation, but just as many such studies failing to show benefit. Less evidence supports the combination of two ‘non-clozapine’ drugs. However, there is more consistent emerging data supporting aripiprazole for helping reduce medication induced weight-gain and reregulate lipid profiles. Effects on cognition do not appear to be favourable and polypharmacy is associated with more side effects. The quantity and quality of the research literature is surprisingly sparse. Clinicians can use selective evidence to support polypharmacy; but the overall context does not support this. Currently there are no clear predictors to suggest which subgroup of patients may be more likely to benefit most from such prescribing. In conclusion, polypharmacy should be carried out with caution with careful baseline and on-going monitoring of the target symptoms, the apriori rationale for initiating treatment with a deadline for cessation, accompanied by a robust assessment of adverse effects and physical health checks.
Keywords: Schizophrenia